Review of types of biomass as a fuel-combustion feedstock and their characteristics - Nugroho Adi Sasongko; Nurjaman Gunadi Putra; Maya Larasati Donna Wardani (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2023)
Biomass is organic matter produced through photosynthetic techniques, each within the form of products and waste. Biomass energy sources have several benefits; amongst others, renewable power to provide sustainable energy sources. Biomass resources are all organic materials that can be renewed, including plants and trees specifically for that energy, food crops, agricultural waste, forestry waste and waste, aquatic plants, animal waste, urban waste, and other waste materials. Improvements in agriculture will lead to increased biomass yields, reduced processing charges, and stepped forward environmental best. Biomass material handling systems constitute a considerable share of investment capital and operating costs in bioenergy conversion facilities. The future improvement of biomass utilization for electricity is collectively burning biomass in current coal boilers and introducing high-efficiency blended-cycle gasification systems, mobile gasoline systems, and modular systems. The use of biomass as gas is more environmentally friendly than fossil fuels. Some types of biomass can be used as a fuel with certain characteristics, such as rice husks and sawdust which will be reviewed in this review. Biomass, as a substitute for coal used as fuel for power plants, has almost similar specifications to coal. Where the value of HHV coal is 5217 kcal/kg (adb) while rice husk, teak sawdust, and Ironwood sawdust have HHV values respectively 3380 kcal/kg (adb), 4460 kcal/kg (adb), and 4465 kcal / kg (adb). Other tests conducted are volatile content, fixed carbon, moisture, and dust content.